The effect of early administration of antibiotics or feeding a diet containing a coccidiostat on inflammatory responses and the morphological structure of selected organs of the immune system in young meat-type turkeys - Radosław Smagieł; Katarzyna Ognik; Ewelina Cholewińska; Anna Stępniowska; Piotr Listos; Bartłomiej Tykałowski; Dariusz Mikulski; Andrzej Koncicki; Jan Jankowski (Poultry Science, 2023)
ABSTRACT: It was assumed that early administration of enrofloxacin or doxycycline may impair immune function and alter the morphology of organs of the immune system in turkeys, and that diets containing the coccidiostat monensin, an ionophore antibiotic, can exert similar effects. The aim of this study was to determine whether early antibiotic administration or feeding a diet containing a coccidiostat affect immune function in young turkeys. The experiment had a completely randomized design, with 8 groups (a total of 3,080 one-day-old turkeys), 7 replicate pens per group and 55 birds per pen. The experiment had a 2-factorial design, with 4 treatments (C—control, M—monensin, E—enrofloxacin, and D—doxycycline) and 2 groups of birds (vaccinated and unvaccinated) per treatment. Control group birds did not receive the coccidiostat or antibiotics. Group M was administered monensin at 90 mg/kg feed for the first 5 d of life, group E received enrofloxacin at 10 mg/kg BW, added to drinking water, for the first 5 d of life, and group D received doxycycline at 50 mg/kg BW, added to drinking water, for the first 5 d of life. One-day old turkeys from groups C+, M+, E+, and D+ were administered live-attenuated vaccines against turkey rhinotracheitis (TRT) (Poulvac TRT; Zoetis, Parsippany, NJ) and Newcastle disease (ND) (Nobilis ND clone 30; Merck, Rahway, NJ) by coarse spray; 28-day-old birds were administered a subcutaneously injected inactivated vaccine against Ornithobacterium rhinotracheale (ORT) (Ornitin, Phibro, Poland). Turkeys from groups C−, M−, E−, and D− were not vaccinated. It was found that early administration of enrofloxacin or doxycycline, or feeding a diet containing monensin, did not weaken the immune system of turkeys. The administration of monensin, in particular when combined with vaccination, was least effective in inhibiting inflammatory responses. Histological changes in immunocompetent organs (fatty degeneration) were also most severe in birds receiving monensin, followed by those administered doxycycline and enrofloxacin. The observed changes were exacerbated by vaccination.